2018
DOI: 10.1002/jcb.27826
|View full text |Cite
|
Sign up to set email alerts
|

Neural stem cell‐derived factors inhibit the growth and invasion of U87 stem‐like cells in vitro

Abstract: Glioma is one of the most common and aggressive tumors in the brain. Significant attention has been paid to the potential use of neural stem/progenitor cells (NSCs/NPCs) as delivery vehicles to cure gliomas. However, whether the NSCs/NPCs or the factors they produced could make a contribution still remains to be seen. In this study, we focused on the inhibitory effects of the factors produced by NSCs/NPCs on the biological behavior of the glioma stem‐like cell in vitro. The human glioma cell line U87 was selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Exosomal lncRNA PTENP1 mediates cell communication and exerts antitumour activity [ 14 ]. Numerous studies have shown that rat NSC‐CM‐induced antiglioma effects are related to the mitogen‐activated protein kinase (MAPK) [ 39 , 40 ] and PI3K/AKT signalling pathways [ 27 ]. The present study demonstrated that human NSC‐CM represses glioma cell progression by downregulating the Wnt/β‐catenin pathway, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosomal lncRNA PTENP1 mediates cell communication and exerts antitumour activity [ 14 ]. Numerous studies have shown that rat NSC‐CM‐induced antiglioma effects are related to the mitogen‐activated protein kinase (MAPK) [ 39 , 40 ] and PI3K/AKT signalling pathways [ 27 ]. The present study demonstrated that human NSC‐CM represses glioma cell progression by downregulating the Wnt/β‐catenin pathway, which is consistent with previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibiting the effects of abnormal Wnt/β‐catenin signalling may be a vital step in preventing glioma progression. Rat embryonic neural stem/progenitor cell (NSC/NPC)‐conditioned medium inhibits U87 cell growth and invasion by downregulating β‐catenin expression [ 27 ]. However, the effects of human NSC‐CM on glioma cell progression remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In another report, cultures containing U87 stem-like cells in contact with an NSC-conditioned medium showed low viability and multiplication of U87 cells without significant modulation of their astrocytic differentiation capacity. Moreover, the invasive and migratory functions of U87 stem-like cells were also reduced [60].…”
Section: Effects Of Neural Stem Cells In Gliomamentioning
confidence: 99%
“…The continued assessment showed the presence of NPCs 20 days after the injection. The neuropathological study of the brains showed that the transplanted stem cells were exclusively in inflammatory regions of neurodegeneration and not in normal tissue, suggesting their potential role in the reversal of the inflammatory process [60]. Finally, the implementation of exogenous human NSCs into the dentate gyrus can also activate the production of endogenous NSCs [58].…”
Section: Neuroprotective and Neurotrophic Functions Of Neural Stem Cells Therapymentioning
confidence: 99%
“…In another report, contact with NSCs conditioned medium containing U87 stem cells (a glioma cell line) showed a lower survival rate and proliferation of U87 cells, and no significant regulatory effect on astrocyte differentiation. In addition, the invasion and migration of U87 stem cells were also reduced [ 56 ]. These suggest that normal NSCs may play a direct role in GBM.…”
Section: Preclinical and Clinical Evidence Of Svz As The Potential Th...mentioning
confidence: 99%